2011
DOI: 10.1186/1471-2369-12-54
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplant survival in pediatric and young adults

Abstract: BackgroundThere is a perception that kidney transplant recipients transferred from pediatric centers to adult care have an increased risk of graft loss. It is not clear whether young adults transplanted in adult centers also suffer from high graft loss rates.MethodsWe examined death censored graft survival in 3 cohorts of young patients transplanted at a single center. Pediatric (PED) patients transplanted at the pediatric center were compared to a cohort of young adults (YAD; age 18- < 25) and a cohort of adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
2
18
1
2
Order By: Relevance
“…Earlier reports support the concept of worsening graft survival and medication adherence following transfer of care from pediatric to adult transplant services. On the contrary, more recent investigations did not find a difference between rates of acute allograft rejection and graft loss before and after transfer . To clarify the possible effect of transfer on the well‐being of transplant patients, it may be worth exploring not only hard outcomes, such as graft loss, but also some intermediate outcomes, such as adherence.…”
mentioning
confidence: 99%
“…Earlier reports support the concept of worsening graft survival and medication adherence following transfer of care from pediatric to adult transplant services. On the contrary, more recent investigations did not find a difference between rates of acute allograft rejection and graft loss before and after transfer . To clarify the possible effect of transfer on the well‐being of transplant patients, it may be worth exploring not only hard outcomes, such as graft loss, but also some intermediate outcomes, such as adherence.…”
mentioning
confidence: 99%
“…However, this may simply reflect higher risks during emerging adulthood [29,30]. Even emerging adults cared for exclusively in an adult-oriented care environment have a heightened risk of graft failure [31]. Likely, a mismatch between the needs of individuals in the high risk age period and the care environment results in the high rate of adverse outcomes following transfer of care: individuals transferred at \21 years of age had a 57 % higher risk of graft failure compared with those transferred at C21 years [6 • ].…”
Section: Medical Outcomesmentioning
confidence: 99%
“…Interestingly, Kiberd et al. found that transfer per se was not a problem point for renal transplant recipients, but that vulnerability to poor outcomes increases during the overall time period of transition. This review focuses on transition broadly as well as the specific transfer from pediatrics.…”
Section: Transition Among Emerging Adults With a Solid Organ Transplantmentioning
confidence: 99%